Sonidegib potentiates the cancer cells' sensitivity to cytostatic agents by functional inhibition of ABCB1 and ABCG2 in vitro and ex vivo - Zhang, Yu; Vagiannis, Dimitrios; Budagaga, Youssif; Sabet, Ziba; Hanke, Ivo; Rozkoš, Tomáš; Hofman, Jakub (Biochemical pharmacology, 2022)
Sonidegib (LDE-225) is a Hedgehog pathway inhibitor used for the therapy of basal cell carcinoma. In addition, the drug is a subject of clinical trials for the treatment of other solid tumors including non-small cell lung cancer (NSCLC). In this study, we explored the potential of sonidegib to act as a perpetrator of drug-drug interactions (DDIs) and modulator of transporter- and enzyme-mediated multidrug resistance (MDR). First, we found that transport functions of ABCB1 and ABCG2 were effectively inhibited by sonidegib in accumulation studies. In contrast, the drug did not cause fluctuations in mRNA levels of tested efflux transporters. In drug combination assays, sonidegib synergistically enhanced the cytotoxicity of daunorubicin and mitoxantrone in ABCB1- and ABCG2-overexpressing cells, respectively. Notably, similar phenomena were also observed in explant tumor cultures derived from NSCLC-suffering patients. In addition, the anticancer effects of sonidegib were not hampered by the expression of the ABC transporters associated with MDR. Last, sonidegib had no significant influence on the activity of CYP3A4 isoform in vitro. In summary, our work suggests that sonidegib can be considered a potential perpetrator of clinical DDIs on ABCB1 and ABCG2. After in vivo evaluation, its chemosensitizing properties might be projected into efficient and safe treatment regimen for the clinical management of NSCLC patients with high ABCB1/ABCG2 expression.
Keywords: nádory plic; nemalobuněčný karcinom plic; proteiny hedgehog; Lung Neoplasms; nádorové proteiny; Humans; ATP Binding Cassette Transporter, Subfamily G, Member 2; Carcinoma, Non-Small-Cell Lung; cytostatické látky; Cytochrome P450; Antineoplastic Agents; Biphenyl Compounds; bifenylové sloučeniny; lidé; ATP Binding Cassette Transporter, Subfamily B; chemorezistence; Pyridines; Non-small cell lung cancer; Hedgehog Proteins; ABC transporter; P-glykoproteiny; Pharmacokinetic resistance; pyridiny; nádorové buněčné linie; protinádorové látky; Sonidegib; Cytostatic Agents; Cell Line, Tumor; Neoplasm Proteins; ABC transportér z rodiny G, člen 2; Drug Resistance, Neoplasm